Role of Invertebrate Biological Origin in Chitin Nanocrystal’s Morphology, Chirality, and Self-Assembly - Kaya, Murat; Yu, Kui; Hansen, Kine Østnes; Al-dubai, Mohammed; So̷rensen, Martin Vinther; Mujtaba, Muhammad (American Chemical Society (ACS), 2025)
The mention of chitin often evokes the Bouligand structure, which is a unique twisted configuration featuring a uniaxial planar organization of fibers. Although a large number of studies focused on Arthropoda, the architecture of chitin in many other invertebrate phyla remains largely unexplored. Herein, we unveil the distinctive architectures of chitin in both Arthropoda and Bryozoa, offering a comparative analysis of the morphological properties of native fibers and chitin nanocrystals sourced from these divergent organisms. In stark contrast to the Bouligand architecture prevalent in Arthropoda, Bryozoa exhibits a unique spiderweb-like arrangement of nanobundle structures, exclusive to this animal group. Bryozoan chitin nanofibers have a diameter smaller than those found among arthropods. After acid hydrolysis, the bryozoan nanocrystals are shorter and have a diameter smaller than those from arthropods. Although the chitin nanocrystals formed the chiral nematic phase, in the current study with the applied methodology, this was not the case with chitin nanocrystals from the studied bryozoan species. The unique chitin nanoarchitecture observed in Bryozoa could serve as an inspiration to produce advanced materials. Their smaller chitin nanocrystals can serve as a potential alternative to those of arthropods.
Keywords: Article